Exploring the Phenotypic and Genetic Characteristics of Respiratory Infections Caused by Moraxella Catarrhalis - Hasan , Noor Flayyih; H J , Burak; Faraj , Hussein Amer (American Journal of Biology and Natural Sciences, 2025)
Investigating the virulence genes of Moraxella catarrhalis in the respiratory system was the goal of this investigation. Baghdad Medical City received sixteen (60) swabs that were taken from individuals with respiratory tract disorders. Three (5%) out of 60 (100%) Moraxella catarrhalis-caused respiratory tract infections in patients and tested positive for the bacteria using the USP A1, cop B, and omp CD. According to the research's findings, Moraxella catarrhalis is harmful to humans If the respiratory system is separated from it. Additionally, all isolates of Moraxella catarrhalis share the characteristics of Usp A1, Cop B, and Omp CD. Future molecular investigations were therefore required to compare Moraxella isolated as a pathogen or normal flora, as well as to examine certain virulence factors and the antibiogram profile at the molecular level.